Fluorescent Quinolinium Derivative as Novel Mitochondria Probe and Function Modulator by Targeting Mitochondrial RNA - Bo-Zheng Wang; Ying-Chen Zhou; Yu-Wei Lin; Xiu-Cai Chen; Ze-Yi Yu; Yao-Hao Xu; Jia-Heng Tan; Zhi-Shu Huang; Shuo-Bin Chen (Molecules, 2023)
Mitochondria have a crucial role in regulating energy metabolism and their dysfunction has been linked to tumorigenesis. Cancer diagnosis and intervention have a great interest in the development of new agents that target biomolecules within mitochondria. However, monitoring and modulating mitochondria RNA (mtRNA), an essential component in mitochondria, in cells is challenging due to limited functional research and the absence of targeting agents. In this study, we designed and synthesized a fluorescent quinolinium derivative, QUCO-1, which actively lit up with mtRNA in both normal and cancer cells in vitro. Additionally, we evaluated the function of QUCO-1 as an mtRNA ligand and found that it effectively induced severe mitochondrial dysfunction and OXPHOS inhibition in RKO colorectal cancer cells. Treatment with QUCO-1 resulted in apoptosis, cell cycle blockage at the G2/M phase, and the effective inhibition of cell proliferation. Our findings suggest that QUCO-1 has great potential as a promising probe and therapeutic agent for mtRNA, with the potential for treating colorectal cancer.